Removal of greenhouse gas in biofilter using organic and inorganic media - Tung, Nguyen Thanh; Chiemchaisri, Wilai; Chiemchaisri, Chart; Sanguanpak, Samunya (Vietnam Journal of Science, Technology and Engineering, 2021)
A biofilter using organic (compost) and inorganic (pumice, porous silica pellet or poremat) media was applied to the removal of methane (CH4) and nitrous oxide (N2O) to minimize the impact of off-gasses from municipal solid waste disposal global. The objective was to determine the appropriate biofilter media for CH4 oxidation and N2O conversion. The off gas (59.6% CH4, 1.0% N2O) was fed simultaneously with air (1:3 ratio) into the biofilter. CH4 oxidation and N2O conversion rates were observed over a 101-day period through the analysis of gas concentration along the biofilter’s depth using gas chromatography. Higher CH4 oxidation in the biofilters containing organic and inorganic media was achieved, especially for the compost-poremat biofilter with 70.1 g CH4/m3/d realised. The most active methane oxidation zone was found near the gas inlet at the bottom of the biofilter. The presence of inorganic material helped promote aerobic conditions for CH4 oxidation, especially during the initial period. N2O was also more completely removed with the biofilter containing inorganic media. Higher methanotrophic activities in matured biofilter media and the presence of methanotrophs type I, which prefer oxygen-rich conditions, were confirmed.